Economic value and characteristics of cloud pharmacy for children based on internet hospital in western China during the COVID-19 pandemic: Cross-sectional survey study - Bin Yang; Bin Yang; Bin Yang; Bin Yang; Qiang Wen; Qiang Wen; Qiang Wen; Qiang Wen; Yi Zhang; Yi Zhang; Yi Zhang; Yi Zhang; et al. (Frontiers Media S.A., 2022)
BackgroundOnline health care services have been encouraged by the Chinese government in recent years, and the COVID-19 pandemic catalyzed the rapid growing of internet hospitals. As an integral part of online health care services, little is known about the economic value and characteristics of cloud pharmacy especially for children. This study aimed to reveal the economic value and comprehensive characteristics of pediatric cloud pharmacy during the COVID-19 pandemic in a tertiary children's hospital in western China.MethodsA total of 33,254 online prescriptions over the course of February 2020 through December 2021 were analyzed with respect to the user profiles, diseases, consulting behaviors, distribution of departments, delivery region and distance, drug information and degree of satisfaction. The cost savings for patients calculated lost wages and the high-speed railway fees for transport to and from hospital.ResultsA total of 33,254 prescriptions, including 56,216 drugs were delivered to 27 provinces and municipalities of China. The internet cloud pharmacy saved a total of more than RMB 11.17 million in financial costs for patients. Of the 33,254 delivered prescriptions, 50.40% were sent to Chongqing Province, the top 5 provinces for out-of-province prescription deliveries were Sichuan (37.77%), Guizhou (8.00%), Yunnan (1.18%), Hubei (0.66%) and Guangdong (0.42%). In terms of department distribution, neurology (31.7%), respiratory (15.0%) and endocrinology (14.6%) were the top three departments. Epilepsy (16.2%), precocious puberty (10.3%) and asthma (8.7%) were the top three frequently consulted diseases. The peak times of day for online prescriptions occurred at 9 AM and 8 PM. 99.67% of users gave full marks for their internet counseling.ConclusionThe pediatric cloud pharmacy is efficient, cost-saving and convenient for children with chronic disease or mild symptoms during the COVID-19 pandemic. The widespread use of this pediatric cloud pharmacy can help alleviating pressure on offline hospitals and facilitated people's lives beyond geographical and time-related limitations. Further efforts are needed to be made to improve the quality and acceptance of pediatric cloud pharmacy, as well as to regulate and standardize the management of this novel online health care service.